Separation and purification of nylon 54 salts from fermentation broth by an integrated process involving microfiltration, ultrafiltration, and ion exchange - Zhao, Xiaojie; Hu, Qixu; Yang, Yue; Feng, Jiao; Wang, Xin; Li, Ganlu; Li, Hui; Chen, Kequan (Frontiers in Bioengineering and Biotechnology, 2024)
Nylon 54 is a novel, biodegradable polyamide with excellent thermal resistance and water absorption properties. It can be polymerized using bio-based cadaverine and succinic acid as monomers. Traditional separation methods isolate individual monomers from the fermentation broth through acidification or alkalization, resulting in significant amounts of waste salts; however, synchronous separation of dibasic acids and diamines has not been reported. This study investigated an integrated process for the separation and extraction of nylon 54 salts from a co-fermentation broth without acidification or alkalization. We meticulously optimized the operational parameters of the integrated process to achieve maximum separation efficiency. Following microfiltration, ultrafiltration, and decolorization, the bacterial eliminating rate was ≥99.83%, and the protein concentration was ≤40 mg/L. The absorbance of the decolorized solution was ≤0.021 at 430 nm, and the recovery rate of nylon 54 salt reached 97%. Then, the pretreated solution was passed through sequential chromatographic columns, which effectively removed organic acid by-products (such as acetic acid and lactic acid), SO4 2-, and NH4 + from the fermentation broth, resulting in a cadaverine yield of 98.01% and a succinic acid yield of 89.35%. Finally, by concentrating and crystallizing the eluent, the simulated fermentation broth yielded nylon 54 salt with a purity of 99.16% and a recovery rate of 58%, and the real fermentation broth yielded nylon 54 salt with a purity of 98.10% and a recovery rate of 56.21%. This integrated process offers a sustainable and environmentally friendly pathway for the complete biosynthesis of nylon 54 salt and has the potential to be extended to the preparation of other nylon salts.FIGURE 1 An integrated process for separating cadaverine and succinic acid from a cofermentation broth.